2020
DOI: 10.1016/j.neuron.2020.04.020
|View full text |Cite
|
Sign up to set email alerts
|

MCH Neurons Regulate Permeability of the Median Eminence Barrier

Abstract: Summary Melanin-concentrating hormone (MCH)-expressing neurons are key regulators of energy and glucose homeostasis. Here, we demonstrate that they provide dense projections to the median eminence (ME) in close proximity to tanycytes and fenestrated vessels. Chemogenetic activation of MCH neurons as well as optogenetic stimulation of their projections in the ME enhance permeability of the ME by increasing fenestrated vascular loops and enhance leptin action in the arcuate nucleus of the hypothalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 57 publications
2
46
0
9
Order By: Relevance
“…During fasting, the tanycyte interface is reshaped to improve the access of metabolic signals to the ARH and to induce meal initiation (30). This reorganization could be induced by tanycytes themselves through metabolic sensing (30) as well as by neurons (32). Second, tanycytes are also able to modulate neuronal functions by releasing both orexigenic and anorexigenic molecules, what we will call "tanykines," into the hypothalamic parenchyma such as diazepam-binding inhibitor (DBI) (33,34), purines (26,28,35,36), triiodothyronine (T3) (37), chemerin (38), and prostaglandin E2 (PGE2) (39) (Fig.…”
Section: Tanycytes Regulate Food Intakementioning
confidence: 99%
“…During fasting, the tanycyte interface is reshaped to improve the access of metabolic signals to the ARH and to induce meal initiation (30). This reorganization could be induced by tanycytes themselves through metabolic sensing (30) as well as by neurons (32). Second, tanycytes are also able to modulate neuronal functions by releasing both orexigenic and anorexigenic molecules, what we will call "tanykines," into the hypothalamic parenchyma such as diazepam-binding inhibitor (DBI) (33,34), purines (26,28,35,36), triiodothyronine (T3) (37), chemerin (38), and prostaglandin E2 (PGE2) (39) (Fig.…”
Section: Tanycytes Regulate Food Intakementioning
confidence: 99%
“…Neuronal regulation of brain endothelial function also occurs in areas without a BBB. Thus, Jiang et al [31] found that melanin-concentrating hormone-expressing neurons regulate the permeability of blood vessels of the median eminence via vascular endothelial growth factor signaling. Another type of BBB regulation can occur with parenchymal cell death.…”
Section: Neurovascular Unitmentioning
confidence: 99%
“…First order neurons, such as AgRPand POMC-neurons, have an exquisite location close to the capillary loops arising from the ME (Schaeffer et al, 2013), with a tightly regulated permeability that allows central access of circulating molecules via CVOs (Banks, 2019;Prevot et al, 2018). Permeability of the ME vascular loops reaching the ARC is tightly regulated by tanycytes, which are glucosesensing cells (Frayling et al, 2011) and one of the main sources of VEGF-A in the ME (Jiang et al, 2020;Langlet et al, 2013a;Langlet et al, 2013b). The tanycytes regulate the direct access of blood-borne molecules to ARC neurons by controlling capillary fenestration.…”
Section: Surprisingly Peripheral Insulin Injection Accelerated the Amentioning
confidence: 99%
“…In conditions of nutrient overload or uncontrolled plasma glucose, systemic VEGF-A could bypass tanycytic-born VEGF-A signaling, thus leading to local adaptations in the ARC. A recent study shows that activation of melanin-concentrating hormone (MCH) neurons in the lateral hypothalamic area also regulates ME/ARC vessels' permeability possibly via the release of VEGF-A (Jiang et al, 2020). However, because insulin has been shown to have a strong inhibitory effect on MCH neurons (Silva et al, 2009), they are unlikely to be involved in the hypoglycemia/insulin-promoted facilitation of the access of GLP1-R agonists to the ARC.…”
Section: Surprisingly Peripheral Insulin Injection Accelerated the Amentioning
confidence: 99%